The effect of heavy strength training on muscle mass and physical performance in elite cross country skiers - Losnegard, T.; Mikkelsen, K.; Ronnestad, B. R.; Hallen, J.; Rud, B.; Raastad, T. (Scandinavian Journal of Medicine & Science in Sports, 2011)
To investigate the effect of supplementing high-volume endurance training with heavy strength training on muscle adaptations and physical performance in elite cross country skiers. Eleven male (18-26 years) and eight female (18-27 years) were assigned to either a strength group (STR) (n=9) or a control group (CON) (n=10). STR performed strength training twice a week for 12 weeks in addition to their normal endurance training. STR improved 1 repetition maximum (RM) for seated pull-down and half squat (19±2% and 12±2%, respectively), while no change was observed in CON. Cross-sectional area (CSA) increased in m. triceps brachii for both STR and CON, while there was no change in the m. quadriceps CSA. VO2max during skate-rollerskiing increased in STR (7±1%), while VO2max during running was unchanged. No change was observed in energy consumption during rollerskiing at submaximal intensities. Double-poling performance improved more for STR than for CON. Both groups showed a similar improvement in rollerski time-trial performance. In conclusion, 12 weeks of supplemental heavy strength training improved the strength in leg and upper body muscles, but had little effect on the muscle CSA in thigh muscles. The supplemental strength training improved both VO2max during skate-rollerskiing and double-poling performance.